2018
DOI: 10.14740/cr655w
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Coping Strategies With Stress in Patients With Acute Myocardial Infarction and Individuals Without a History of Fixed Myocardial Infarction

Abstract: BackgroundThis study aimed at investigating the coping strategies with stress in patients with acute myocardial infarction (MI) and individuals without a history of fixed MI and cardiovascular disorders.MethodsThis case-control crossover study was conducted from March 2015 to February 2016 on 220 patients with acute MI (MI patients) as case group and 220 patients without any history of MI and cardiovascular diseases as the control group using availability sampling method. To collect the required data, demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Among the respondents, the task-oriented style (TOC) was dominant, which is associated with a lower CVD risk, and the prevalence of the TOC style was higher among officers. The style of emotions-oriented (EOC) and avoidance-oriented (AOC) and mixed EOC + AOC that are associated with a higher level of stress and a higher risk of CVD [34,35] occurred in a total of 20% of respondents. The study shows a correlation between the occurrence of EOC and a positive family history of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Among the respondents, the task-oriented style (TOC) was dominant, which is associated with a lower CVD risk, and the prevalence of the TOC style was higher among officers. The style of emotions-oriented (EOC) and avoidance-oriented (AOC) and mixed EOC + AOC that are associated with a higher level of stress and a higher risk of CVD [34,35] occurred in a total of 20% of respondents. The study shows a correlation between the occurrence of EOC and a positive family history of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Coping strategy is a significant moderating variable which influences the level of negative perception of stress in case of stressful events. 28 Parent's answer to stress seems to be dependent on coping styles. 29 Emotional and avoidant coping styles are normally considered maladaptive if compared to task-oriented strategies that seem to be more active and efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in Taiwan with participation of 100 post-CABG surgery patients, Problem-Focused Thinking was found the most used coping strategy by the patients. [6] Sadr Bafghi et al [21] reported that 53.6% of with acute myocardial infarction patients used emotion-focused coping strategy and who used emotion-focused coping strategy had negative perceived stress. Also they stated in study that people with higher levels of stress are more likely to use inefficient coping strategies.…”
Section: Discussionmentioning
confidence: 99%